2018
DOI: 10.1111/hepr.13046
|View full text |Cite
|
Sign up to set email alerts
|

Serum Wisteria floribunda agglutinin‐positive Mac‐2 binding protein more reliably distinguishes liver fibrosis stages in non‐alcoholic fatty liver disease than serum Mac‐2 binding protein

Abstract: This head-to-head comparison suggests that WFA -M2BP is superior to M2BP for distinguishing liver fibrosis stages in NAFLD patients. A marked discrepancy between the two biomarkers may be indicative of advanced NAFLD (UMIN000023286).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Differences in measurement times may have caused errors in the results and the low accuracy of serum M2BPGi-based fibrosis diagnosis in our study (median [range] of M2BPGi was 0.6 [0.13-5.90]]. In a Japanese study examining M2BPGi in NAFLD [27], the serum M2BPGi COI was 0.85 (0.22-11.32), slightly higher than the present data; however, another study showed different serum M2BPGi COIs for non-HCC and HCC NAFLD (1.1 ± 0.7 and 3.1 ± 3.2, respectively) [4]. Fourth, this study was retrospective in nature, and, as TE was not conducted for all patients, TE data could not be analyzed.…”
Section: Discussionmentioning
confidence: 69%
“…Differences in measurement times may have caused errors in the results and the low accuracy of serum M2BPGi-based fibrosis diagnosis in our study (median [range] of M2BPGi was 0.6 [0.13-5.90]]. In a Japanese study examining M2BPGi in NAFLD [27], the serum M2BPGi COI was 0.85 (0.22-11.32), slightly higher than the present data; however, another study showed different serum M2BPGi COIs for non-HCC and HCC NAFLD (1.1 ± 0.7 and 3.1 ± 3.2, respectively) [4]. Fourth, this study was retrospective in nature, and, as TE was not conducted for all patients, TE data could not be analyzed.…”
Section: Discussionmentioning
confidence: 69%
“…Several unique studies have provided the means for a non‐invasive screening of liver fibrosis in HIV/HCV coinfection, using the macrophage activation marker soluble CD163 or surface‐enhanced laser desorption ionization time‐of‐flight mass spectrometry . In the present study we focused on WFA + ‐M2BP, which has multibranching and sialylated N‐glycans, and is well known as a marker of liver fibrosis for use in various types of liver disease, including hepatitis B, hepatitis C, and non‐alcoholic fatty liver disease . In liver surgery, Ishii et al .…”
Section: Discussionmentioning
confidence: 99%
“…As an index of insulin resistance, the homeostasis model assessment-insulin resistance (HOMA-IR) was calculated using the following equation: HOMA-IR = fasting insulin (μU/mL) × plasma glucose (mg/dL)/405 [27]. Hyaluronic acid [28], type IV collagen 7s domain [29, 30], and Wisteria floribunda agglutinin positive Mac-2-binding protein (WFA + -M2B) [3032], all of which have been reported as useful liver fibrosis markers in NAFLD, were measured. In addition, the fibrosis scores such as the FIB-4 index [33] and NAFLD fibrosis scorer (NFS) [34] were calculated, as reported previously.…”
Section: Methodsmentioning
confidence: 99%